Preparation method of high-hardness polycarbonate composite material

By adding cerium elements and modified fillers to the polycarbonate material, the wear resistance of polycarbonate materials is solved by forming amino functional groups and isocyanate groups, and combining polyethylene terephthalate components rich in end carboxyl groups is solved. and the problem of insufficient strength has achieved the improvement of high strength and wear resistance, and is suitable for high-end products.

CN119144136APending Publication Date: 2024-12-17ZHUZHOU DIBO PHOTOELECTRIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410988038.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The wear resistance and strength of ordinary polycarbonate materials are poor, making it difficult to meet the production technical requirements of high-end products, especially when high strength and wear resistance are required.

Method used

By adding fillers such as cerium elements and modifying fillers with chemical substances such as 3-aminopropyltrimethoxysilane and 4,4'-methylenebis(phenyl isocyanate), amino functional groups and isocyanate groups are formed. Combining 2,5-furandicarboxylic acid to prepare polyethylene terephthalate-rich end carboxylic acid, improve the binding strength and density of component A and filler powder, and enhance the tensile strength of polycarbonate composite materials and wear resistance.

Benefits of technology

It significantly improves the tensile strength and wear resistance of polycarbonate composite materials, making them suitable for situations with high strength requirements, extends the service life of the material, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-hardness polycarbonate composite material. The preparation method comprises the following steps: (1) preparing basic powder; (2) modifying to prepare filler powder; (3) mixing 2, 5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and an antioxidant 1010, and performing esterification and polycondensation to obtain a component A; and (4) uniformly mixing the component A, the filler powder and the polycarbonate granules, drying the mixture at 100 DEG C for more than 10 hours, then carrying out melt blending on the mixture in a torque rheometer at the blending temperature of 270 + / -5 DEG C and the rotating speed of 60 r / min, and after blending, carrying out pressurized injection molding at the injection molding temperature of 280 + / -5 DEG C in an injection molding machine to obtain the polycarbonate composite material. The polycarbonate composite material prepared by the method disclosed by the invention has high tensile strength and wear resistance, so that the polycarbonate material can be used for occasions with higher strength requirements, the wear resistance is improved, the polycarbonate material is not easy to wear, the durability of the material is improved, and the maintenance cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polycarbonate composite materials, and in particular to a method for preparing a high-hardness polycarbonate composite material. Background Art

[0002] In recent years, filled composite materials with lightweight materials and simple production processes have gradually become a hot research direction. Polycarbonate, as a polymer engineering plastic, stands out for its multiple excellent properties such as light weight, excellent corrosion resistance and easy production and processing. It is widely used in electronic components, electrical housings and other electronic and electrical products. However, ordinary PC has relatively poor wear resistance and strength, but the production technology requirements of high-end products are high, which makes ordinary PC unable to be used in many fields. Therefore, in order to improve the performance of PC materials, fillers such as carbon materials, inorganic oxides or metals are often added. These fillers can be distributed in the polymer matrix, which is conducive to the improvement of the performance of the entire composite material. Summary of the invention

[0003] To this end, the present invention provides a method for preparing a high-hardness polycarbonate composite material, the preparation steps comprising:

[0004] (1) preparing an ammonia solution; preparing an ethanol solution of tetrabutyl titanate and ethylene glycol; preparing an aqueous solution of cerium nitrate; stirring the ammonia solution, then adding the tetrabutyl titanate and ethylene glycol ethanol solution to the solution under stirring, continuing to stir for more than 10 minutes after the addition is completed, then continuing to add the aqueous solution of cerium nitrate to the solution under stirring, continuing to stir for more than 10 minutes after the addition is completed to obtain a mixed solution, placing the mixed solution in a reaction kettle, sealing the reaction kettle, and then heating to 150-160° C. and keeping it warm for more than 8 hours, air cooling to room temperature after the insulation is completed, and then opening the reaction kettle, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying at 60° C. for more than 2 hours to obtain a base powder;

[0005] (2) adding the base powder to anhydrous ethanol, stirring for more than 30 minutes under an ultrasonic environment to obtain a suspension, and then adding 3-aminopropyltrimethoxysilane to the suspension under stirring. After the addition is completed, heating in a water bath to 60±3°C, keeping warm for more than 3 hours, and then separating the solid and the liquid. The solid phase is washed with ethanol for more than 3 times, and dried at 60°C for more than 2 hours. The dried solid phase is added to N,N-dimethylformamide, and the solution is stirred for more than 20 minutes. Then, 4,4'-methylenebis(phenyl isocyanate) is added to the solution under stirring. After the addition is completed, heating in a water bath to 80±2°C and keeping warm for more than 2 hours. Condensation and reflux are carried out during the insulation process. After the insulation is completed, the solid and the liquid are separated. The solid phase is washed with N,N-dimethylformamide for more than two times, washed with deionized water for more than two times, and then dried at 60°C for more than 2 hours to obtain a filler powder;

[0006] (3) In a polymerization kettle, 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 are uniformly mixed, the polymerization kettle is sealed, nitrogen is introduced to discharge the air in the polymerization kettle, so that the polymerization kettle is in a nitrogen protection environment, and then heated to 240-250° C. for esterification reaction. When water begins to be distilled out, it is the esterification zero point, and when the amount of distilled water reaches 95% of the theoretical water output, it is the esterification end point; then vacuum is drawn to keep the pressure in the polymerization kettle at 80 Pa, and then the temperature is raised to 280° C. with stirring to carry out polycondensation reaction. When the power of the stirring motor reaches 80 W, the polymerization kettle is processed and pelletized to obtain component A;

[0007] (4) The component A, filler powder and polycarbonate pellets are mixed uniformly, and the mixture is dried at 100° C. for more than 10 hours. The mixture is then melt-blended in a torque rheometer at a blending temperature of 270±5° C. and a rotation speed of 60 r / min. After blending, the mixture is pressurized and injection molded at an injection molding temperature of 280±5° C. in an injection molding machine to obtain the polycarbonate composite material.

[0008] Furthermore, in the step (1), in the aqueous ammonia solution, the mass percentage of the solute is 15% to 18%, and the solvent is water; in the ethanol solution of tetrabutyl titanate and ethylene glycol, the mass percentage of tetrabutyl titanate is 6% to 8%, the mass percentage of ethylene glycol is 3% to 4%, and the solvent is ethanol; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 35 to 40 g / L, and the solvent is water.

[0009] Furthermore, in the step (1), the volume ratio of the tetrabutyl titanate, the ethanol solution of ethylene glycol and the aqueous solution of cerium nitrate added to the aqueous ammonia solution is ammonia solution:tetrabutyl titanate, the ethanol solution of ethylene glycol:the aqueous solution of cerium nitrate=10:2-3:0.8-1.

[0010] Furthermore, in the step (2), the mass ratio of the base powder added to the anhydrous ethanol is base powder: anhydrous ethanol = 1:50; the mass ratio of 3-aminopropyltrimethoxysilane added to the suspension to the mass ratio of the base powder in the suspension is base powder: 3-aminopropyltrimethoxysilane = 1:2 to 3.

[0011] Furthermore, in the step (2), the mass ratio of the dried solid phase added to N,N-dimethylformamide is the dried solid phase: N,N-dimethylformamide = 1:100; the mass ratio of the added 4,4'-methylenebis(phenyl isocyanate) to the solid phase in the solution is the solid phase: 4,4'-methylenebis(phenyl isocyanate) = 1:0.3-0.4.

[0012] Furthermore, in the step (3), the mass ratio of 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 is 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 = 5-6: 20-25: 12-15: 0.3-0.4: 0.01-0.02.

[0013] Furthermore, in the step (4), the mass ratio of the component A, filler powder and polycarbonate pellets is component A: filler powder: polycarbonate pellets = 17:3:80.

[0014] Furthermore, in the step (4), the pressure of the pressure injection molding is 120 MPa.

[0015] The beneficial effects of the present invention are as follows: the polycarbonate composite material prepared by the method of the present invention has high tensile strength and wear resistance, so that the polycarbonate material can be used in occasions with high strength requirements, and the wear resistance is improved, it is not easy to wear, the durability of the material is improved, and the maintenance cost is reduced. The present invention improves the strength and wear resistance of polycarbonate by adding fillers. First, cerium elements are doped in the fillers to increase the specific surface area of ​​the fillers, improve the surface energy of the fillers, and provide conditions for subsequent further processing. Then, the fillers are modified by 3-aminopropyltrimethoxysilane to form a large number of amino functional groups on the surface of the fillers, and then the isocyanate groups are grafted by 4,4'-methylenebis(phenyl isocyanate); on the other hand, a polyethylene terephthalate component rich in terminal carboxyl groups is prepared by adding 2,5-furandicarboxylic acid, and the high reactivity of the isocyanate group and the terminal carboxyl group is utilized to achieve reactive compatibilization of component A and filler powder, improve the bonding strength and density of component A and filler powder, and reduce interphase defects. At the same time, the modified filler can significantly improve the wettability with the polycarbonate matrix, enhance the bonding strength between the filler and the matrix, and play a good second phase reinforcement effect. DETAILED DESCRIPTION

[0016] The present invention will be further described below in conjunction with the embodiments.

[0017] Example 1

[0018] A method for preparing a high-hardness polycarbonate composite material, the preparation steps comprising:

[0019] (1) preparing an ammonia aqueous solution; in which the mass percentage of the solute in the ammonia aqueous solution is 15%, and the solvent is water; preparing an ethanol solution of tetrabutyl titanate and ethylene glycol; in which the mass percentage of tetrabutyl titanate and ethylene glycol in the ethanol solution is 6%, the mass percentage of ethylene glycol in the ethanol solution is 3%, and the solvent is ethanol; preparing an aqueous solution of cerium nitrate; in which the concentration of cerium nitrate in the aqueous solution is 35 g / L, and the solvent is water; stirring the ammonia aqueous solution, and then adding the ethanol solution of tetrabutyl titanate and ethylene glycol to the solution under stirring, continuing to stir for 10 minutes after the addition is completed, and then The aqueous solution of cerium nitrate is continuously added to the solution under stirring, and the volume ratio of the tetrabutyl titanate, the ethanol solution of ethylene glycol, and the aqueous solution of cerium nitrate added to the aqueous ammonia solution is ammonia solution: tetrabutyl titanate, the ethanol solution of ethylene glycol: aqueous solution of cerium nitrate = 10:2:0.8; after the addition is completed, stirring is continued for 10 minutes to obtain a mixed solution, the mixed solution is placed in a reactor, the reactor is sealed, and then heated to 150° C. and kept warm for 8 hours, after the insulation is completed, it is air-cooled to room temperature, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and dried at 60° C. for 2 hours to obtain a base powder;

[0020] (2) adding the base powder to anhydrous ethanol, the mass ratio of the base powder to the anhydrous ethanol being 1:50; stirring for 30 min under an ultrasonic environment (300 W, 40 kHz) to obtain a suspension, and then adding 3-aminopropyltrimethoxysilane to the suspension under stirring, the mass ratio of 3-aminopropyltrimethoxysilane added to the suspension to the mass ratio of the base powder in the suspension being 1:2; heating in a water bath to 60±3° C. after the addition is completed, keeping warm for 3 h, then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, drying at 60° C. for 2 h, and adding the dried solid phase to N,N-dimethylformamide , the mass ratio of the dried solid phase added to N,N-dimethylformamide is the dried solid phase: N,N-dimethylformamide = 1:100; the solution is stirred for 20 minutes, and then 4,4'-methylenebis(phenyl isocyanate) is added to the solution under stirring, and the mass ratio of the added 4,4'-methylenebis(phenyl isocyanate) to the solid phase in the solution is solid phase: 4,4'-methylenebis(phenyl isocyanate) = 1:0.3; after the addition is completed, the water bath is heated to 80±2°C and kept warm for 2 hours, condensed and refluxed during the insulation process, and the solid-liquid separation is completed after the insulation is completed, the solid phase is washed twice with N,N-dimethylformamide, washed twice with deionized water, and then dried at 60°C for 2 hours to obtain filler powder;

[0021] (3) in a polymerization kettle, 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 are uniformly mixed, and the mass ratio of 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 is 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 = 5:20:12:0.3:0.01; the polymerization kettle is sealed, nitrogen is filled into the polymerization kettle to exhaust the air in the polymerization kettle, so that the polymerization kettle is in a nitrogen protection environment, and then heated to 250° C. for esterification reaction. When distilled water begins to appear, it is the esterification zero point, and when the distilled water reaches 95% of the theoretical water output, it is the esterification end point; then vacuuming the polymerization kettle to maintain the pressure at 80 Pa, and then heating to 280° C. and stirring to carry out polycondensation reaction. When the power of the stirring motor reaches 80 W, the polymerization kettle is processed and pelletized to obtain component A;

[0022] (4) The component A, filler powder and polycarbonate pellets are mixed uniformly, wherein the mass ratio of the component A, filler powder and polycarbonate pellets is component A: filler powder: polycarbonate pellets = 17:3:80; the mixture is dried at 100° C. for 10 h, and then the mixture is melt-blended in a torque rheometer at a blending temperature of 270±5° C. and a rotation speed of 60 r / min. After blending, the mixture is pressurized and injection molded at an injection molding temperature of 280±5° C. in an injection molding machine at a pressure of 120 MPa to obtain the polycarbonate composite material.

[0023] Example 2

[0024] A method for preparing a high-hardness polycarbonate composite material, the preparation steps comprising:

[0025] (1) preparing an ammonia aqueous solution; in which the mass percentage of the solute in the ammonia aqueous solution is 15%, and the solvent is water; preparing an ethanol solution of tetrabutyl titanate and ethylene glycol; in which the mass percentage of tetrabutyl titanate and the ethanol solution of ethylene glycol is 7%, the mass percentage of ethylene glycol is 3%, and the solvent is ethanol; preparing an aqueous solution of cerium nitrate; in which the concentration of cerium nitrate in the aqueous solution of cerium nitrate is 35 g / L, and the solvent is water; stirring the ammonia aqueous solution, and then adding the ethanol solution of tetrabutyl titanate and ethylene glycol to the solution under stirring, continuing to stir for 10 minutes after the addition is completed, and then The aqueous solution of cerium nitrate is continuously added to the solution under stirring, and the volume ratio of the tetrabutyl titanate, the ethanol solution of ethylene glycol, and the aqueous solution of cerium nitrate added to the aqueous ammonia solution is ammonia solution: tetrabutyl titanate, the ethanol solution of ethylene glycol: aqueous solution of cerium nitrate = 10:2:0.9; after the addition is completed, stirring is continued for 10 minutes to obtain a mixed solution, the mixed solution is placed in a reactor, the reactor is sealed, and then heated to 150° C. and kept warm for 8 hours, after the insulation is completed, it is air-cooled to room temperature, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and dried at 60° C. for 2 hours to obtain a base powder;

[0026] (2) adding the base powder to anhydrous ethanol, the mass ratio of the base powder to the anhydrous ethanol being 1:50; stirring for 30 min under an ultrasonic environment (300 W, 40 kHz) to obtain a suspension, and then adding 3-aminopropyltrimethoxysilane to the suspension under stirring, the mass ratio of 3-aminopropyltrimethoxysilane added to the suspension to the mass ratio of the base powder in the suspension being 1:2; heating in a water bath to 60±3° C. after the addition is completed, keeping warm for 3 h, then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, drying at 60° C. for 2 h, and adding the dried solid phase to N,N-dimethylformamide , the mass ratio of the dried solid phase added to N,N-dimethylformamide is the dried solid phase: N,N-dimethylformamide = 1:100; the solution is stirred for 20 minutes, and then 4,4'-methylenebis(phenyl isocyanate) is added to the solution under stirring, and the mass ratio of the added 4,4'-methylenebis(phenyl isocyanate) to the solid phase in the solution is solid phase: 4,4'-methylenebis(phenyl isocyanate) = 1:0.3; after the addition is completed, the water bath is heated to 80±2°C and kept warm for 2 hours, condensed and refluxed during the insulation process, and the solid-liquid separation is completed after the insulation is completed, the solid phase is washed twice with N,N-dimethylformamide, washed twice with deionized water, and then dried at 60°C for 2 hours to obtain filler powder;

[0027] (3) in a polymerization kettle, 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 are uniformly mixed, and the mass ratio of 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 is 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 = 5:22:13:0.3:0.01; the polymerization kettle is sealed, nitrogen is filled into the polymerization kettle to exhaust the air in the polymerization kettle, so that the polymerization kettle is in a nitrogen protection environment, and then heated to 250° C. for esterification reaction. When distilled water begins to appear, it is the esterification zero point, and when the distilled water reaches 95% of the theoretical water output, it is the esterification end point; then vacuuming the polymerization kettle to maintain the pressure at 80 Pa, and then heating to 280° C. and stirring to carry out polycondensation reaction. When the power of the stirring motor reaches 80 W, the polymerization kettle is processed and pelletized to obtain component A;

[0028] (4) The component A, filler powder and polycarbonate pellets are mixed uniformly, wherein the mass ratio of the component A, filler powder and polycarbonate pellets is component A: filler powder: polycarbonate pellets = 17:3:80; the mixture is dried at 100° C. for 10 h, and then the mixture is melt-blended in a torque rheometer at a blending temperature of 270±5° C. and a rotation speed of 60 r / min. After blending, the mixture is pressurized and injection molded at an injection molding temperature of 280±5° C. in an injection molding machine at a pressure of 120 MPa to obtain the polycarbonate composite material.

[0029] Example 3

[0030] A method for preparing a high-hardness polycarbonate composite material, the preparation steps comprising:

[0031] (1) preparing an ammonia aqueous solution; in which the mass percentage of the solute in the ammonia aqueous solution is 18%, and the solvent is water; preparing an ethanol solution of tetrabutyl titanate and ethylene glycol; in which the mass percentage of tetrabutyl titanate and ethylene glycol in the ethanol solution is 7%, the mass percentage of ethylene glycol in the ethanol solution is 4%, and the solvent is ethanol; preparing an aqueous solution of cerium nitrate; in which the concentration of cerium nitrate in the aqueous solution is 40 g / L, and the solvent is water; stirring the ammonia aqueous solution, and then adding the ethanol solution of tetrabutyl titanate and ethylene glycol to the solution under stirring, continuing to stir for 10 minutes after the addition is completed, and then The aqueous solution of cerium nitrate is continuously added to the solution under stirring, and the volume ratio of the tetrabutyl titanate, the ethanol solution of ethylene glycol, and the aqueous solution of cerium nitrate added to the aqueous ammonia solution is ammonia solution: tetrabutyl titanate, the ethanol solution of ethylene glycol: aqueous solution of cerium nitrate = 10:3:0.9; after the addition is completed, stirring is continued for 10 minutes to obtain a mixed solution, the mixed solution is placed in a reactor, the reactor is sealed, and then heated to 150° C. and kept warm for 8 hours, after the insulation is completed, it is air-cooled to room temperature, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and dried at 60° C. for 2 hours to obtain a base powder;

[0032] (2) adding the base powder to anhydrous ethanol, the mass ratio of the base powder to the anhydrous ethanol being 1:50; stirring for 30 min under an ultrasonic environment (300 W, 40 kHz) to obtain a suspension, and then adding 3-aminopropyltrimethoxysilane to the suspension under stirring, the mass ratio of 3-aminopropyltrimethoxysilane added to the suspension to the mass ratio of the base powder in the suspension being 1:3; heating in a water bath to 60±3° C. after the addition is completed, keeping warm for 3 h, then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, drying at 60° C. for 2 h, and adding the dried solid phase to N,N-dimethylformamide , the mass ratio of the dried solid phase added to N,N-dimethylformamide is the dried solid phase: N,N-dimethylformamide = 1:100; the solution is stirred for 20 minutes, and then 4,4'-methylenebis(phenyl isocyanate) is added to the solution under stirring, and the mass ratio of the added 4,4'-methylenebis(phenyl isocyanate) to the solid phase in the solution is solid phase: 4,4'-methylenebis(phenyl isocyanate) = 1:0.4; after the addition is completed, the water bath is heated to 80±2°C and kept warm for 2 hours, condensed and refluxed during the insulation process, and the solid-liquid separation is completed after the insulation is completed, the solid phase is washed twice with N,N-dimethylformamide, washed twice with deionized water, and then dried at 60°C for 2 hours to obtain filler powder;

[0033] (3) in a polymerization kettle, 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 are uniformly mixed, and the mass ratio of 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 is 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 = 6:24:14:0.4:0.02; the polymerization kettle is sealed, nitrogen is filled into the polymerization kettle to exhaust the air in the polymerization kettle, so that the polymerization kettle is in a nitrogen protection environment, and then heated to 250° C. for esterification reaction. When distilled water begins to appear, it is the esterification zero point, and when the distilled water reaches 95% of the theoretical water output, it is the esterification end point; then vacuuming the polymerization kettle to maintain the pressure at 80 Pa, and then heating to 280° C. and stirring to carry out polycondensation reaction. When the power of the stirring motor reaches 80 W, the polymerization kettle is processed and pelletized to obtain component A;

[0034] (4) The component A, filler powder and polycarbonate pellets are mixed uniformly, wherein the mass ratio of the component A, filler powder and polycarbonate pellets is component A: filler powder: polycarbonate pellets = 17:3:80; the mixture is dried at 100° C. for 10 h, and then the mixture is melt-blended in a torque rheometer at a blending temperature of 270±5° C. and a rotation speed of 60 r / min. After blending, the mixture is pressurized and injection molded at an injection molding temperature of 280±5° C. in an injection molding machine at a pressure of 120 MPa to obtain the polycarbonate composite material.

[0035] Example 4

[0036] A method for preparing a high-hardness polycarbonate composite material, the preparation steps comprising:

[0037] (1) preparing an ammonia aqueous solution; in which the mass percentage of the solute in the ammonia aqueous solution is 18%, and the solvent is water; preparing an ethanol solution of tetrabutyl titanate and ethylene glycol; in which the mass percentage of tetrabutyl titanate and ethylene glycol in the ethanol solution is 8%, the mass percentage of ethylene glycol in the ethanol solution is 4%, and the solvent is ethanol; preparing an aqueous solution of cerium nitrate; in which the concentration of cerium nitrate in the aqueous solution is 40 g / L, and the solvent is water; stirring the ammonia aqueous solution, and then adding the ethanol solution of tetrabutyl titanate and ethylene glycol to the solution under stirring, and continuing to stir for 10 minutes after the addition is completed, and then The aqueous solution of cerium nitrate is continuously added to the solution under stirring, and the volume ratio of the tetrabutyl titanate, the ethanol solution of ethylene glycol, and the aqueous solution of cerium nitrate added to the aqueous ammonia solution is ammonia solution: tetrabutyl titanate, the ethanol solution of ethylene glycol: aqueous solution of cerium nitrate = 10:3:1; after the addition is completed, stirring is continued for 10 minutes to obtain a mixed solution, the mixed solution is placed in a reactor, the reactor is sealed, and then heated to 150° C. and kept warm for 8 hours, after the insulation is completed, it is air-cooled to room temperature, and then the reactor is opened for solid-liquid separation, the solid phase is washed with deionized water 3 times, and dried at 60° C. for 2 hours to obtain a base powder;

[0038] (2) adding the base powder to anhydrous ethanol, the mass ratio of the base powder to the anhydrous ethanol being 1:50; stirring for 30 min under an ultrasonic environment (300 W, 40 kHz) to obtain a suspension, and then adding 3-aminopropyltrimethoxysilane to the suspension under stirring, the mass ratio of 3-aminopropyltrimethoxysilane added to the suspension to the mass ratio of the base powder in the suspension being 1:3; heating in a water bath to 60±3° C. after the addition is completed, keeping warm for 3 h, then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, drying at 60° C. for 2 h, and adding the dried solid phase to N,N-dimethylformamide , the mass ratio of the dried solid phase added to N,N-dimethylformamide is the dried solid phase: N,N-dimethylformamide = 1:100; the solution is stirred for 20 minutes, and then 4,4'-methylenebis(phenyl isocyanate) is added to the solution under stirring, and the mass ratio of the added 4,4'-methylenebis(phenyl isocyanate) to the solid phase in the solution is solid phase: 4,4'-methylenebis(phenyl isocyanate) = 1:0.4; after the addition is completed, the water bath is heated to 80±2°C and kept warm for 2 hours, condensed and refluxed during the insulation process, and the solid-liquid separation is completed after the insulation is completed, the solid phase is washed twice with N,N-dimethylformamide, washed twice with deionized water, and then dried at 60°C for 2 hours to obtain filler powder;

[0039] (3) in a polymerization kettle, 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 are uniformly mixed, and the mass ratio of 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 is 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 = 6:25:15:0.4:0.02; the polymerization kettle is sealed, nitrogen is filled into the polymerization kettle to exhaust the air in the polymerization kettle, so that the polymerization kettle is in a nitrogen protection environment, and then heated to 250° C. for esterification reaction. When distilled water begins to appear, it is the esterification zero point, and when the distilled water reaches 95% of the theoretical water output, it is the esterification end point; then vacuuming the polymerization kettle to keep the pressure at 80 Pa, and then heating to 280° C. and stirring to carry out polycondensation reaction. When the power of the stirring motor reaches 80 W, the polymerization kettle is processed and pelletized to obtain component A;

[0040] (4) The component A, filler powder and polycarbonate pellets are mixed uniformly, wherein the mass ratio of the component A, filler powder and polycarbonate pellets is component A: filler powder: polycarbonate pellets = 17:3:80; the mixture is dried at 100° C. for 10 h, and then the mixture is melt-blended in a torque rheometer at a blending temperature of 270±5° C. and a rotation speed of 60 r / min. After blending, the mixture is pressurized and injection molded at an injection molding temperature of 280±5° C. in an injection molding machine at a pressure of 120 MPa to obtain the polycarbonate composite material.

[0041] Comparative Example 1

[0042] A method for preparing a polycarbonate composite material as a comparison, the preparation steps comprising:

[0043] (1) preparing an ammonia solution; in the ammonia solution, the mass percentage of the solute is 18%, and the solvent is water; preparing an ethanol solution of tetrabutyl titanate and ethylene glycol; in the ethanol solution of tetrabutyl titanate and ethylene glycol, the mass percentage of tetrabutyl titanate is 7%, the mass percentage of ethylene glycol is 4%, and the solvent is ethanol; stirring the ammonia solution, and then adding the ethanol solution of tetrabutyl titanate and ethylene glycol to the solution under stirring, and continuing to stir for 10 minutes after the addition is completed, the volume ratio of the ethanol solution of tetrabutyl titanate and ethylene glycol added to the ammonia solution is ammonia solution: tetrabutyl titanate, ethanol solution of ethylene glycol = 10:3; after the addition is completed, continuing to stir for 10 minutes to obtain a mixed solution, placing the mixed solution in a reactor, sealing the reactor, and then heating to 150° C. and keeping it warm for 8 hours, air cooling to room temperature after the insulation is completed, and then opening the reactor, separating the solid and liquid, washing the solid phase with deionized water 3 times, and drying at 60° C. for 2 hours to obtain the base powder of this comparative example;

[0044] (2) adding the base powder to anhydrous ethanol, the mass ratio of the base powder to the anhydrous ethanol being 1:50; stirring for 30 min under an ultrasonic environment (300 W, 40 kHz) to obtain a suspension, and then adding 3-aminopropyltrimethoxysilane to the suspension under stirring, the mass ratio of 3-aminopropyltrimethoxysilane added to the suspension to the mass ratio of the base powder in the suspension being 1:3; heating in a water bath to 60±3° C. after the addition is completed, keeping warm for 3 h, then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, drying at 60° C. for 2 h, and adding the dried solid phase to N,N-dimethylformamide , the mass ratio of the dried solid phase added to N,N-dimethylformamide is the dried solid phase: N,N-dimethylformamide = 1:100; the solution is stirred for 20 minutes, and then 4,4'-methylenebis(phenyl isocyanate) is added to the solution under stirring, and the mass ratio of the added 4,4'-methylenebis(phenyl isocyanate) to the solid phase in the solution is solid phase: 4,4'-methylenebis(phenyl isocyanate) = 1:0.4; after the addition is completed, the water bath is heated to 80±2°C and kept warm for 2 hours, condensed and refluxed during the insulation process, and the solid-liquid separation is completed after the insulation is completed, the solid phase is washed twice with N,N-dimethylformamide, washed twice with deionized water, and then dried at 60°C for 2 hours to obtain filler powder;

[0045] (3) in a polymerization kettle, 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 are uniformly mixed, and the mass ratio of 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 is 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 = 6:24:14:0.4:0.02; the polymerization kettle is sealed, nitrogen is filled into the polymerization kettle to exhaust the air in the polymerization kettle, so that the polymerization kettle is in a nitrogen protection environment, and then heated to 250° C. for esterification reaction. When distilled water begins to appear, it is the esterification zero point, and when the distilled water reaches 95% of the theoretical water output, it is the esterification end point; then vacuuming the polymerization kettle to maintain the pressure at 80 Pa, and then heating to 280° C. and stirring to carry out polycondensation reaction. When the power of the stirring motor reaches 80 W, the polymerization kettle is processed and pelletized to obtain component A;

[0046] (4) The component A, filler powder and polycarbonate pellets are mixed uniformly, wherein the mass ratio of the component A, filler powder and polycarbonate pellets is component A: filler powder: polycarbonate pellets = 17:3:80; the mixture is dried at 100°C for 10 hours, and then the mixture is melt-blended in a torque rheometer at a blending temperature of 270±5°C and a rotation speed of 60r / min. After blending, the mixture is pressurized and injection molded at an injection molding temperature of 280±5°C in an injection molding machine at a pressure of 120MPa to obtain the polycarbonate composite material described in this comparative example.

[0047] Comparative Example 2

[0048] A method for preparing a polycarbonate composite material as a comparison, the preparation steps comprising:

[0049] (1) preparing an ammonia aqueous solution; in which the mass percentage of the solute in the ammonia aqueous solution is 18%, and the solvent is water; preparing an ethanol solution of tetrabutyl titanate and ethylene glycol; in which the mass percentage of tetrabutyl titanate and ethylene glycol in the ethanol solution is 7%, the mass percentage of ethylene glycol in the ethanol solution is 4%, and the solvent is ethanol; preparing an aqueous solution of cerium nitrate; in which the concentration of cerium nitrate in the aqueous solution is 40 g / L, and the solvent is water; stirring the ammonia aqueous solution, and then adding the ethanol solution of tetrabutyl titanate and ethylene glycol to the solution under stirring, continuing to stir for 10 minutes after the addition is completed, and then The aqueous solution of cerium nitrate is continuously added to the solution under stirring, and the volume ratio of the tetrabutyl titanate, the ethanol solution of ethylene glycol, and the aqueous solution of cerium nitrate added to the aqueous ammonia solution is ammonia solution: tetrabutyl titanate, the ethanol solution of ethylene glycol: aqueous solution of cerium nitrate = 10:3:0.9; after the addition is completed, stirring is continued for 10 minutes to obtain a mixed solution, the mixed solution is placed in a reactor, the reactor is sealed, and then heated to 150° C. and kept warm for 8 hours, after the insulation is completed, it is air-cooled to room temperature, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and dried at 60° C. for 2 hours to obtain a base powder;

[0050] (2) adding the base powder to anhydrous ethanol, the mass ratio of the base powder to the anhydrous ethanol being 1:50; stirring for 30 min under an ultrasonic environment (300 W, 40 kHz) to obtain a suspension, and then adding 3-aminopropyltrimethoxysilane to the suspension under stirring, the mass ratio of 3-aminopropyltrimethoxysilane added to the suspension to the mass ratio of the base powder in the suspension being 1:3; heating in a water bath to 60±3° C. after the addition is completed, keeping warm for 3 h, then separating the solid and the liquid, washing the solid phase with ethanol 3 times, and drying at 60° C. for 2 h to obtain the filler powder of this comparative example;

[0051] (3) in a polymerization kettle, 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 are uniformly mixed, and the mass ratio of 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 is 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 = 6:24:14:0.4:0.02; the polymerization kettle is sealed, nitrogen is filled into the polymerization kettle to exhaust the air in the polymerization kettle, so that the polymerization kettle is in a nitrogen protection environment, and then heated to 250° C. for esterification reaction. When distilled water begins to appear, it is the esterification zero point, and when the distilled water reaches 95% of the theoretical water output, it is the esterification end point; then vacuuming the polymerization kettle to maintain the pressure at 80 Pa, and then heating to 280° C. and stirring to carry out polycondensation reaction. When the power of the stirring motor reaches 80 W, the polymerization kettle is processed and pelletized to obtain component A;

[0052] (4) The component A, filler powder and polycarbonate pellets are mixed uniformly, wherein the mass ratio of the component A, filler powder and polycarbonate pellets is component A: filler powder: polycarbonate pellets = 17:3:80; the mixture is dried at 100°C for 10 hours, and then the mixture is melt-blended in a torque rheometer at a blending temperature of 270±5°C and a rotation speed of 60r / min. After blending, the mixture is pressurized and injection molded at an injection molding temperature of 280±5°C in an injection molding machine at a pressure of 120MPa to obtain the polycarbonate composite material described in this comparative example.

[0053] Comparative Example 3

[0054] A method for preparing a polycarbonate composite material as a comparison, the preparation steps comprising:

[0055] (1) preparing an ammonia aqueous solution; in which the mass percentage of the solute in the ammonia aqueous solution is 18%, and the solvent is water; preparing an ethanol solution of tetrabutyl titanate and ethylene glycol; in which the mass percentage of tetrabutyl titanate and ethylene glycol in the ethanol solution is 7%, the mass percentage of ethylene glycol in the ethanol solution is 4%, and the solvent is ethanol; preparing an aqueous solution of cerium nitrate; in which the concentration of cerium nitrate in the aqueous solution is 40 g / L, and the solvent is water; stirring the ammonia aqueous solution, and then adding the ethanol solution of tetrabutyl titanate and ethylene glycol to the solution under stirring, continuing to stir for 10 minutes after the addition is completed, and then The aqueous solution of cerium nitrate is continuously added to the solution under stirring, and the volume ratio of the tetrabutyl titanate, the ethanol solution of ethylene glycol, and the aqueous solution of cerium nitrate added to the aqueous ammonia solution is ammonia solution: tetrabutyl titanate, the ethanol solution of ethylene glycol: aqueous solution of cerium nitrate = 10:3:0.9; after the addition is completed, stirring is continued for 10 minutes to obtain a mixed solution, the mixed solution is placed in a reactor, the reactor is sealed, and then heated to 150° C. and kept warm for 8 hours, after the insulation is completed, it is air-cooled to room temperature, and then the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and dried at 60° C. for 2 hours to obtain a base powder;

[0056] (2) adding the base powder to anhydrous ethanol, the mass ratio of the base powder to the anhydrous ethanol being 1:50; stirring for 30 min under an ultrasonic environment (300 W, 40 kHz) to obtain a suspension, and then adding 3-aminopropyltrimethoxysilane to the suspension under stirring, the mass ratio of 3-aminopropyltrimethoxysilane added to the suspension to the mass ratio of the base powder in the suspension being 1:3; heating in a water bath to 60±3° C. after the addition is completed, keeping warm for 3 h, then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, drying at 60° C. for 2 h, and adding the dried solid phase to N,N-dimethylformamide , the mass ratio of the dried solid phase added to N,N-dimethylformamide is the dried solid phase: N,N-dimethylformamide = 1:100; the solution is stirred for 20 minutes, and then 4,4'-methylenebis(phenyl isocyanate) is added to the solution under stirring, and the mass ratio of the added 4,4'-methylenebis(phenyl isocyanate) to the solid phase in the solution is solid phase: 4,4'-methylenebis(phenyl isocyanate) = 1:0.4; after the addition is completed, the water bath is heated to 80±2°C and kept warm for 2 hours, condensed and refluxed during the insulation process, and the solid-liquid separation is completed after the insulation is completed, the solid phase is washed twice with N,N-dimethylformamide, washed twice with deionized water, and then dried at 60°C for 2 hours to obtain filler powder;

[0057] (3) terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 are uniformly mixed in a polymerization kettle, wherein the mass ratio of terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 is terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 = 24:14:0.4:0.02; the polymerization kettle is sealed, nitrogen is introduced to discharge the air in the polymerization kettle, so that the polymerization kettle is in a nitrogen protection environment, and then heated to 250° C. for esterification reaction. The esterification zero point is when distilled water begins to appear, and the esterification end point is when the distilled water reaches 95% of the theoretical water output; then vacuuming the polymerization kettle to maintain the pressure at 80 Pa, and then heating to 280° C. for polycondensation reaction. When the power of the stirring motor reaches 80 W, the mixture is processed and pelletized to obtain component A;

[0058] (4) The component A, filler powder and polycarbonate pellets are mixed uniformly, wherein the mass ratio of the component A, filler powder and polycarbonate pellets is component A: filler powder: polycarbonate pellets = 17:3:80; the mixture is dried at 100°C for 10 hours, and then the mixture is melt-blended in a torque rheometer at a blending temperature of 270±5°C and a rotation speed of 60r / min. After blending, the mixture is pressurized and injection molded at an injection molding temperature of 280±5°C in an injection molding machine at a pressure of 120MPa to obtain the polycarbonate composite material described in this comparative example.

[0059] Example 5

[0060] The composite materials prepared by the methods described in the above test embodiments and comparative examples were processed into tensile specimens, and tensile tests were carried out respectively in accordance with the requirements of standard GB / T1040-2018 to test the tensile strength, and the tensile speed was set to 10 mm / min. The wear resistance of the composite materials prepared by the methods described in the above test embodiments and comparative examples was tested using a reciprocating sliding friction and wear tester. The friction frequency was set to 1 Hz, the pressure was 8 kN during the friction process, and the total friction sliding distance was set to 160 m. The specific wear rate Φ was calculated, Φ = (mass difference before and after sample wear) / (sample density × 160 × 8), where 160 is the total friction sliding distance, and 8 is the pressure applied during the friction process. The results are shown in Table 1.

[0061] As shown in Table 1, the polycarbonate composite material prepared by the method of the present invention has high tensile strength and wear resistance, so that the polycarbonate material can be used in occasions with high strength requirements, and the wear resistance is improved, not easy to wear, the durability of the material is improved, and the maintenance cost is reduced. The present invention improves the strength and wear resistance of polycarbonate by adding fillers. First, cerium is doped in the filler to increase the specific surface area of ​​the filler, improve the surface energy of the filler, and provide conditions for subsequent further processing. Then, the filler is modified by 3-aminopropyltrimethoxysilane to form a large number of amino functional groups on the surface of the filler, and then the isocyanate group is grafted by 4,4'-methylenebis(phenyl isocyanate); on the other hand, a polyethylene terephthalate component rich in terminal carboxyl groups is prepared by adding 2,5-furandicarboxylic acid, and the high reactivity of the isocyanate group and the terminal carboxyl group is utilized to achieve reactive compatibilization of component A and filler powder, improve the bonding strength and density of component A and filler powder, and reduce interphase defects. At the same time, the modified filler can significantly improve the wettability with the polycarbonate matrix, enhance the bonding strength between the filler and the matrix, and play a good second phase reinforcement effect.

[0062] Table 1

[0063] Experimental Group Tensile strength(MPa) <![CDATA[Specific wear rate Φ (×10 -3 mm 3 / kN·m)]]> Example 1 57.4 26.5 Example 2 58.3 26.2 Example 3 59.1 25.8 Example 4 58.6 26.0 Comparative Example 1 50.9 43.4 Comparative Example 2 47.5 84.1 Comparative Example 3 49.3 58.7

[0064] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for preparing a high-hardness polycarbonate composite material, It is characterized in that The preparation steps include: (1) preparing an ammonia solution; preparing an ethanol solution of tetrabutyl titanate and ethylene glycol; preparing an aqueous solution of cerium nitrate; stirring the ammonia solution, then adding the tetrabutyl titanate and ethylene glycol ethanol solution to the solution under stirring, continuing to stir for more than 10 minutes after the addition is completed, then continuing to add the aqueous solution of cerium nitrate to the solution under stirring, continuing to stir for more than 10 minutes after the addition is completed to obtain a mixed solution, placing the mixed solution in a reaction kettle, sealing the reaction kettle, and then heating to 150-160° C. and keeping it warm for more than 8 hours, air cooling to room temperature after the insulation is completed, and then opening the reaction kettle, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying at 60° C. for more than 2 hours to obtain a base powder; (2) adding the base powder to anhydrous ethanol, stirring for more than 30 minutes under an ultrasonic environment to obtain a suspension, and then adding 3-aminopropyltrimethoxysilane to the suspension under stirring. After the addition is completed, heating in a water bath to 60±3°C, keeping warm for more than 3 hours, and then separating the solid and the liquid. The solid phase is washed with ethanol for more than 3 times, and dried at 60°C for more than 2 hours. The dried solid phase is added to N,N-dimethylformamide, and the solution is stirred for more than 20 minutes. Then, 4,4'-methylenebis(phenyl isocyanate) is added to the solution under stirring. After the addition is completed, heating in a water bath to 80±2°C and keeping warm for more than 2 hours. Condensation and reflux are carried out during the insulation process. After the insulation is completed, the solid and the liquid are separated. The solid phase is washed with N,N-dimethylformamide for more than two times, washed with deionized water for more than two times, and then dried at 60°C for more than 2 hours to obtain a filler powder; (3) In a polymerization kettle, 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 are uniformly mixed, the polymerization kettle is sealed, nitrogen is introduced to discharge the air in the polymerization kettle, so that the polymerization kettle is in a nitrogen protection environment, and then heated to 240-250° C. for esterification reaction. When water begins to be distilled out, it is the esterification zero point, and when the amount of distilled water reaches 95% of the theoretical water output, it is the esterification end point; then vacuum is drawn to keep the pressure in the polymerization kettle at 80 Pa, and then the temperature is raised to 280° C. with stirring to carry out polycondensation reaction. When the power of the stirring motor reaches 80 W, the polymerization kettle is processed and pelletized to obtain component A; (4) The component A, filler powder and polycarbonate pellets are mixed uniformly, and the mixture is dried at 100° C. for more than 10 hours. The mixture is then melt-blended in a torque rheometer at a blending temperature of 270±5° C. and a rotation speed of 60 r / min. After blending, the mixture is pressurized and injection molded at an injection molding temperature of 280±5° C. in an injection molding machine to obtain the polycarbonate composite material.

2. A method for preparing a high-hardness polycarbonate composite material according to claim 1, It is characterized in that In the step (1), in the aqueous ammonia solution, the mass percentage of the solute is 15% to 18%, and the solvent is water; in the ethanol solution of tetrabutyl titanate and ethylene glycol, the mass percentage of tetrabutyl titanate is 6% to 8%, the mass percentage of ethylene glycol is 3% to 4%, and the solvent is ethanol; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 35 to 40 g / L, and the solvent is water.

3. A method for preparing a high-hardness polycarbonate composite material according to claim 2, It is characterized in that In the step (1), the volume ratio of the tetrabutyl titanate, the ethanol solution of ethylene glycol and the aqueous solution of cerium nitrate added to the aqueous ammonia solution is ammonia solution:tetrabutyl titanate, the ethanol solution of ethylene glycol:the aqueous solution of cerium nitrate=10:2-3:0.8-1.

4. The method for preparing a high-hardness polycarbonate composite material according to claim 1, It is characterized in that In the step (2), the mass ratio of the base powder added to the anhydrous ethanol is base powder: anhydrous ethanol = 1:50; the mass ratio of 3-aminopropyltrimethoxysilane added to the suspension to the mass ratio of the base powder in the suspension is base powder: 3-aminopropyltrimethoxysilane = 1:2-3.

5. A method for preparing a high-hardness polycarbonate composite material according to claim 4, It is characterized in that In the step (2), the mass ratio of the dried solid phase added to N,N-dimethylformamide is the dried solid phase: N,N-dimethylformamide = 1:100; the mass ratio of the added 4,4'-methylenebis(phenyl isocyanate) to the solid phase in the solution is the solid phase: 4,4'-methylenebis(phenyl isocyanate) = 1:0.3-0.

4.

6. The method for preparing a high-hardness polycarbonate composite material according to claim 1, It is characterized in that In the step (3), the mixing mass ratio of 2,5-furandicarboxylic acid, terephthalic acid, ethylene glycol, ethylene glycol antimony and antioxidant 1010 is 2,5-furandicarboxylic acid: terephthalic acid: ethylene glycol: ethylene glycol antimony: antioxidant 1010 = 5-6: 20-25: 12-15: 0.3-0.4: 0.01-0.

02.

7. The method for preparing a high-hardness polycarbonate composite material according to claim 1, It is characterized in that In the step (4), the mass ratio of component A, filler powder and polycarbonate pellets is component A: filler powder: polycarbonate pellets = 17:3:

80.

8. The method for preparing a high-hardness polycarbonate composite material according to claim 1, It is characterized in that In the step (4), the pressure of the pressure injection molding is 120 MPa.